A rare case of cellular angiofibroma affecting the periurethral region in a 38-year-old woman. (14th September 2018) - Kumar, Prem; Singh, Smita; Kumar, Abhishek; Janoria, Somesh
Abstract : Cellular angiofibroma (CAF) is a rare, site-specific, benign mesenchymal tumour affecting both women and men in the genitourinary region. The tumour usually presents as a small, asymptomatic lesion involving the vulvovaginal regions in women and inguinoscrotal regions in men. We report the case of a 38-year-old woman presenting with a painless mass in the vulval region, especially on the right side of urethral meatus for 8 years with progressively increasing lower abdominal discomfort. A simple excision was performed. The diagnosis of CAF was confirmed histopathologically.